Analysis of the antimicrobial potential of sericin‐coated silver nanoparticles against human pathogens. Issue 3 (29th December 2022) - Mumtaz, Shumaila; Ali, Shaukat; Kazmi, Syed Akif Raza; Mughal, Tafail Akbar; Mumtaz, Samaira; Tahir, Hafiz Muhammad; Summer, Muhammad; Ara, Chaman; Rashid, Muhammad Imran
Abstract: The antibacterial activity of synthetic antimicrobial agents is well known, but most of them have several side effects and are effective against selective microbes. Recently, major concern for the microbiologists is to investigate for some stable, non‐toxic, cheap, and eco‐friendly antimicrobial agents with a wide range of bactericidal potential. A cost‐effective and environmentally friendly alternate has been proposed in the form of green synthesized nanoparticles. The Present study was designed to fabricate sericin‐coated silver nanoparticles (S‐AgNPs) using sericin as stabilizer and reductant of silver ions and their antibacterial potential was evaluated at various concentrations and temperatures (8, 40, and 50°C). Antimicrobial activities were assessed by the agar well diffusion method. Antibacterial activity of S‐AgNPs was measured at different concentrations (1–6 mg/ml) whereas; antifungal activity was tested at 5–20 mg/ml of S‐AgNPs. Nanoparticles were characterized by UV–visible spectrophotometer, Fourier transform infrared spectroscopy, and scanning electron microscopy. These nanoparticles significantly subdued the growth of Clostridium difficile (18.7 ± 0.9 mm), Proteus mirabilis (12.3 ± 0.3 mm) and Bacillus licheniformis (10.7 ± 0.9 mm) and Aspergillus flavus (18.7 ± 2.0 mm), Mucor mycetes (13 .0 ± 1.5 mm), Candida albicans (15.3 ± 0.3 mm) and Aspergillus niger (10.0 ± 0.6 mm). S‐AgNPs were stable at all temperatures and the maximum growth inhibition was found at 8°C for all pathogenic strains. We concluded that the S‐AgNPs could be a potential candidate to inhibit the growth of bacterial and fungal pathogens at a wide range of environmental conditions like temperature. In various biomedical applications including antimicrobial and wound dressings, S‐AgNPs can be used in the future to treat various bacterial and fungal infections. Abstract : Schematic summary of the current study Novel, eco‐friendly and cost‐effective silk protein sericin‐conjugated silver nanoparticles were synthesized and characterized. Scanning electron microscopy analysis revealed a small size of sericin conjugated synthesized silver nanoparticles (46.6 nm). The sericin conjugated silver nanoparticles were found effective against various bacterial and fungal pathogens.